Fibroblast growth factor 19 as a countermeasure to muscle and locomotion dysfunctions in experimental cerebral palsy. Issue 6 (26th October 2021) - Pereira, Sabrina da Conceição; Benoit, Bérengère; de Aguiar Junior, Francisco Carlos Amanajás; Chanon, Stéphanie; Vieille‐Marchiset, Aurélie; Pesenti, Sandra; Ruzzin, Jérome; Vidal, Hubert; Toscano, Ana Elisa
Abstract: Background: Cerebral palsy (CP) associates cerebral function damages with strong locomotor defects and premature sarcopenia. We previously showed that fibroblast growth factor 19 (FGF19) exerts hypertrophic effects on skeletal muscle and improves muscle mass and strength in mouse models with muscle atrophy. Facing the lack of therapeutics to treat locomotor dysfunctions in CP, we investigated whether FGF19 treatment could have beneficial effects in an experimental rat model of CP. Methods: Cerebral palsy was induced in male Wistar rat pups by perinatal anoxia immediately after birth and by sensorimotor restriction of hind paws maintained until Day 28. Daily subcutaneous injections with recombinant human FGF19 (0.1 mg/kg bw) were performed from Days 22 to 28. Locomotor activity and muscle strength were assessed before and after FGF19 treatment. At Day 29, motor coordination on rotarod and various musculoskeletal parameters (weight of tibia bone and of soleus and extensor digitorum longus (EDL) muscles; area of skeletal muscle fibres) were evaluated. In addition, expression of specific genes linked to human CP was measured in rat skeletal muscles. Results: Compared to controls, CP rats had reduced locomotion activity (−37.8% of distance travelled, P < 0.05), motor coordination (−88.9% latency of falls on rotarod, P < 0.05) and muscle strength (−25.1%, P < 0.05). These defects were associated with reduction in soleus (−51.5%, P < 0.05) and EDL (−42.5%, P < 0.05) weight, smaller area of muscle fibres, and with lower tibia weight (−38%, P < 0.05). In muscles from rats submitted to CP, changes in the expression levels of several genes related to muscle development and neuromuscular junctions were similar to those found in wrist muscle of children with CP (increased mRNA levels of Igfbp5, Kcnn3, Gdf8, and MyH4 and decreased expression of Myog, Ucp2 and Lpl ). Compared with vehicle‐treated CP rats, FGF19 administration improved locomotor activity (+53.2%, P < 0.05) and muscle strength (+25.7%, P < 0.05), and increased tibia weight (+13.8%, P < 0.05) and soleus and EDL muscle weight (+28.6% and +27.3%, respectively, P < 0.05). In addition, it reduced a number of very small fibres in both muscles ( P < 0.05). Finally, gene expression analyses revealed that FGF19 might counteract the immature state of skeletal muscles induced by CP. Conclusions: These results demonstrate that pharmacological intervention with recombinant FGF19 could restore musculoskeletal and locomotor dysfunction in an experimental CP model, suggesting that FGF19 may represent a potential therapeutic strategy to combat the locomotor disorders associated with CP.